2019
DOI: 10.9734/acri/2019/v18i330137
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, Antioxidant Properties and Sensory Attributes of Golden Melon (Cucumis melon L)-Watermelon (Citrullus lanatus) Juice Blends

Abstract: This study investigates the physico-chemical, antioxidant properties and sensory attributes of golden melon-watermelon fruits juice blends. The juice extracted from golden melon and watermelon fruits were mixed together in different ratios 100% watermelon (GMW 1), 100% golden melon (GMW 2), 50% golden melon and 50% watermelon (GMW 3), 70% golden melon and 30% watermelon (GMW 4), 30% golden melon and 70% watermelon (GMW 5) in order to establish possible synergetic effect. The proximate composition of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…This is in agreement with the previous work of Ndife et al (2013). Sodipo et al (2019) also reported that Iron was found in lowest concentration in all fruit juice samples. Oluyemi et al (2006) reported that in the diet of pregnant women, lactating mothers and babies; iron is important in order to prevent anemia.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…This is in agreement with the previous work of Ndife et al (2013). Sodipo et al (2019) also reported that Iron was found in lowest concentration in all fruit juice samples. Oluyemi et al (2006) reported that in the diet of pregnant women, lactating mothers and babies; iron is important in order to prevent anemia.…”
Section: Resultssupporting
confidence: 94%
“…The total ash content which is the minerals in the form of oxide was between 0.18 and 0.88%. Sodipo et al (2019) reported moisture content of 93.91±0.03 which is higher than 86.10 recorded in this study and protein content of 1.83±0.06 which is lower than 7.10 obtained in this study for watermelon juice. The higher the moisture contents of any food, the greater the risk of microbial contaminant which ultimately leads to faster spoilage (Ozioma et al, 2013).…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…Total phenolic values observed in this study was 333.68mg GAE/100 ml. [35] reported a total phenol content of GAE/100ml for golden melon and that this increased to GAE/150ml with the addition of watermelon.…”
Section: Total Phenolic Content Of the Optimized Samplementioning
confidence: 99%